From anonymous to best-seller: digressions on the success of Project Araribá - História in the PNLD of 2008 (Tempo e Argumento, 2012)
Considering the fact of the collectionProjeto Araribá: História to be one of the most distributed by the PNLD of 2008, the characteristics that made it a unique work and the educational context of the XXI century, this text discusses the aspects related to the constitution, distribution and choice of this work that can explain your success. In this sense, some general characteristics are discussed as: the scope of the collection to variousdisciplines, the objective of developing the reading competence, the collective authorship and the context ofModerna publishing house after the entry of the Spanish group Santillana. In order to expand the discussion, we seek to understand, outside the purpose of developing the reading competence, the presentation of the collectionin the PNLD of 2008, the aggressive sales strategies and the collective authorship as identity of the collection. It is concluded that the success of this collection harnesses to complex relationships between the current demands for the quality education and the commercial interests, as well between the creation of a tool that seeks to develop proficient reading and the public policies that, somehow, legitimate the purposes of the collection.
Keywords: history and teaching; text-book; projeto araribá; PNLD; reading